Power-Aware Physical Design Methodologies for Advanced Semiconductor Integrated Circuits - Rambabu Mandalapu (International Journal of Computational and Experimental Science and Engineering, 2026)
The rapid evolution of semiconductor integrated circuits toward nanoscale process technologies has fundamentally transformed the design paradigm, elevating power consumption from a secondary consideration to a primary design constraint. Power-aware physical design methodologies have emerged as essential frameworks that systematically integrate power optimization objectives throughout the entire implementation process, addressing the complex challenges posed by escalating dynamic and static power consumption in advanced technology nodes. This article encompasses comprehensive strategies including multi-voltage domain architectures, sophisticated clock management techniques, power-aware placement and routing algorithms, and advanced verification frameworks that ensure power intent preservation. Contemporary developments incorporate machine learning techniques, statistical optimization approaches, and three-dimensional integration technologies that extend power optimization capabilities beyond traditional chip-level boundaries. The integration of power considerations across logical and physical design domains enables coordinated optimization strategies that balance power efficiency with performance requirements while maintaining design robustness across process variations and operating conditions. Advanced packaging techniques and system-level power management strategies provide additional optimization opportunities through heterogeneous integration and cross-layer coordination mechanisms. The article demonstrates that power-aware design methodologies are fundamental enablers for energy-efficient computing systems, supporting the evolving requirements of mobile electronics, data processing systems, and embedded platforms while addressing the sustainability concerns of contemporary semiconductor applications.